2020
DOI: 10.1371/journal.pone.0223086
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of rice wild relatives as a source of traits for adaptation to iron toxicity and enhanced grain quality

Abstract: Rice wild relatives (RWR) constitute an extended gene pool that can be tapped for the breeding of novel rice varieties adapted to abiotic stresses such as iron (Fe) toxicity. Therefore, we screened 75 Oryza genotypes including 16 domesticated O. sativa genotypes, one O. glaberrima, and 58 RWR representing 21 species, for tolerance to Fe toxicity. Plants were grown in a semi-artificial greenhouse setup, in which they were exposed either to control conditions, an Fe shock during the vegetative growth stage (acut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The Tajima neutrality test (D) has also supported this condition, where this germplasm has an indicating the expansion of population size (for example, after a purifying selection or bottleneck) because all sequences have negative values (D<0) (Korneliussen et al, 2013). Consequently, future rice improvement must be oriented to outcrossing, as was employed by Niruntrayakul et al (2009) and Bierschenk et al (2020). According to Gaikward et al (2021), most wild rice relatives have novel beneficial alleles for improving cultivated rice varieties, such as better adaptation to different ecological regimes and biotic and abiotic stresses.…”
Section: Resultsmentioning
confidence: 95%
“…The Tajima neutrality test (D) has also supported this condition, where this germplasm has an indicating the expansion of population size (for example, after a purifying selection or bottleneck) because all sequences have negative values (D<0) (Korneliussen et al, 2013). Consequently, future rice improvement must be oriented to outcrossing, as was employed by Niruntrayakul et al (2009) and Bierschenk et al (2020). According to Gaikward et al (2021), most wild rice relatives have novel beneficial alleles for improving cultivated rice varieties, such as better adaptation to different ecological regimes and biotic and abiotic stresses.…”
Section: Resultsmentioning
confidence: 95%
“…From these and other studies it can be concluded that ample genetic variation for tolerance to Fe toxicity exists within theO. sativa gene pool (Matthus et al 2015;Pawar et al 2021), and that wild relatives may serve as sources of novel traits enhancing adaptation to Fe toxicity (Bierschenk et al 2020;Wairich et al, 2021).…”
Section: Siliconmentioning
confidence: 85%
“…However, no gene with similar function was found in rice despite several efforts ( Sperotto et al, 2009 ; Distelfeld et al, 2012 ; Jeong et al, 2013 ). Therefore, wild relatives of wheat are an interesting source of genetic variability for improving Fe concentration in cultivated wheat varieties, an approach that can be used with wild rice species ( Ricachenevsky and Sperotto, 2016 ; Bierschenk et al, 2020 ; Wairich et al, 2020 ).…”
Section: Genes Controlling Fe Translocation and Loading In Seedsmentioning
confidence: 99%